2021
DOI: 10.11648/j.sjph.20210903.15
|View full text |Cite
|
Sign up to set email alerts
|

Status Quo and Equity of Health Care Resources Allocation in China from 2016 to 2019: An Empirical Analysis

Abstract: Background: With the development of the social economy, medical and health resources in China have increased to varying degrees. However, it is inevitable that health financing and health talents are shifting to developed areas. Because of this, this study analyzes the current situation and equity of China's medical and health institutions from the number of health care institutions, beds in these institutions and health professionals. From the perspective of people needs, it provides a theoretical basis for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the formulation of regional health planning, in addition to the total population of each district, a scientific system configuration mode should be established according to regional area, population density and other influencing factors [4].While narrowing the between regional difference, we should also take the fairness of internal resource allocation into account. Focusing on intra-regional synergy, allocating and integrating regional TCM resource in accordance with the principles of fairness, rationality and efficiency, so as to drive the coordinated development of the whole region [5].…”
Section: Include Geography As An Important Factor In Health Planningmentioning
confidence: 99%
“…In the formulation of regional health planning, in addition to the total population of each district, a scientific system configuration mode should be established according to regional area, population density and other influencing factors [4].While narrowing the between regional difference, we should also take the fairness of internal resource allocation into account. Focusing on intra-regional synergy, allocating and integrating regional TCM resource in accordance with the principles of fairness, rationality and efficiency, so as to drive the coordinated development of the whole region [5].…”
Section: Include Geography As An Important Factor In Health Planningmentioning
confidence: 99%
“…The COVID-19 pandemic has highlighted severe weaknesses in Chinese healthcare systems and a lack of focus on health resource allocation [7]. Previous research has shown that inequalities still exist in the state of health and the use of health services in China [8][9][10]. Guangxi Zhuang Autonomous Region is an ethnic frontier and economically underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches about the distribution of healthcare institutions focused on public institutions and the balance of healthcare resource allocation at various scales, mainly those state-owned ones [ 4 9 ], the descriptive analysis, the Lorenz curve, and the Gini coefficient are widely used to examine the equilibrium of medical resource allocation [ 10 , 11 ], whereas geographic information technologies such as kernel density [ 12 ] and the two-step search method [ 13 15 ] are used to examine the spatial distribution and accessibility of the medical resources [ 16 ]. Obviously, these studies ignored the complementary role of private medical institutions, underestimated the function of their healthcare in China.…”
mentioning
confidence: 99%